LEMONGRASS AND CINNAMON ESSENTIAL OILS AS VITAMIN C PRESERVATIVES AND FLAVOUR ENHANCERS IN JAM - Byarushengo, Denice; Minja, Rwaichi; Temu, Abraham (Tanzania Journal of Engineering and Technology, 2017)
Lemongrass and cinnamon essential oils (LEO and CEO) are natural oils with high anti- oxidation capacity, pleasant flavour, and various health benefits. Their ability to preserve vitamin C and flavour in jam have not been tested. In this study the performance of two essential oils (EOs) in preserving vitamin C and improving jam flavour were investigated. The EOs were produced by hydro-steam distillation of fresh lemongrasses and cinnamon leaves using a Clevenger apparatus. Jam samples were dosed with various concentrations of either single or mixed EOs and then stored at either room or refrigeration temperature. Samples were analysed for changes in vitamin C content and flavour, after every 10 days for 60 days. Vitamin C content was determined using 2,6 dichlorophenol indophenol visual titration method, whereas sensory analysis was done by five semi trained panellists. It was revealed that both LEO and CEO have high potential to reduce loss of vitamin C and impart better flavour in pineapple jam. The improved quality of the jam is due to anti- microbial and anti-oxidant effects of the essential oils as reported in literature. Mixing the EOs had synergistic effect which maximizes their potential to reduce vitamin C loss with lower dose than when used individually. Mixed EOs doses also enhanced the jam flavour.